Assessment of Lateral Compression type 1 pelvic ring injuries by intraoperative manipulation: which fracture pattern is unstable? - Tosounidis, Theodoros; Kanakaris, Nikolaos; Nikolaou, Vasilios; Tan, Boon; Giannoudis, Peter V (Int Orthop, 2012)
PURPOSE: We performed a prospective study to document, by intra-operative manipulation under anaesthesia (MUA) of the pelvic ring, the stability of lateral compression type 1 injuries that were managed in a Level-I Trauma Centre. The documentation of the short-term outcome of the management of these injuries was our secondary aim. METHODS: A total of 63 patients were included in the study. Thirty-five patients (group A) were treated surgically whereas 28 (group B) were managed nonoperatively. Intraoperative rotational instability, evident by more than two centimetres of translation during the manipulation manoeuvre, was combined with a complete sacral fracture in all cases. RESULTS: A statistically significant difference was present between the length of hospital stay, the time to independent pain-free mobilisation, post-manipulation pain levels and opioid requirements between the two groups, with group A demonstrating significantly decreased values in all these four variables (p < 0.05). There was also a significant difference between the pre- and 72-hour post-manipulation visual analogue scale and analgesic requirements of the group A patients, whereas the patients in group B did not demonstrate such a difference. CONCLUSION: LC-1 injuries with a complete posterior sacral injury are inheritably rotationally unstable and patients presenting with these fracture patterns definitely gain benefit from surgical stabilisation.
Keywords: Adolescent; Adult; Aged; Bone Screws; Female; Fracture Fixation, Internal; Fractures, Bone; Humans; Length of Stay; Male; Middle Aged; Monitoring, Intraoperative; Pain Measurement; Pelvic Bones; Prospective Studies; Retrospective Studies; Sacrum; Tomography, X-Ray Computed; Treatment Outcome; Young Adult